ADAPTING THE SOCIAL WORK CURRICULUM FOR RELEVANCE IN A SOUTH AFRICAN UNIVERSITY: A COLLABORATIVE AUTOETHNOGRAPHY OF SOCIAL WORK ACADEMICS DURING THE KZN FLOODS - Motloung, Siphiwe; Mzinyane, Bongane (Social Work/Maatskaplike Werk, 2023)
This article adopts collaborative autoethnography in order to critically reflect on the experiences of social work academics who integrated disaster-specific approaches to the social work curriculum of two undergraduate courses in a South African university. This curriculum adaptation was in response to the KwaZulu-Natal floods of 2022. The integration of topics such as green social work and disaster-specific trauma responses at an undergraduate level of social work is advocated. These collaborative autoethnographic accounts contribute important lessons for social work education, practice and research in the era of natural disasters exacerbated by climate change.